(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article describes phenological observations carried out during the periods of germination, tillering, tube formation, heading, flowering and ripening of autumn rye. The development time of agricultural crops, including rye, depends on the biological characteristics of the plant, as well as the timing of sowing, the geographical and weather conditions of the region chosen for cultivation, the type and type of soil, and the level of provision. with nutrients and may vary depending on the agrotechnical measures used.